StrokeCog Markov Model: Projected Prevalent and Incident Cases of Stroke and Poststroke Cognitive Impairment to 2035 in Ireland. Issue 12 (December 2021) - Sexton, Eithne; Donnelly, Nora-Ann; Merriman, Niamh A.; Hickey, Anne; Wren, Maev-Ann; O'Flaherty, Martin; Bandosz, Piotr; Guzman-Castillo, Maria; Williams, David J.; Horgan, Frances; Pender, Niall; Feeney, Joanne; et al.
Abstract : Background and Purpose: Cognitive impairment no dementia (CIND) and dementia are common stroke outcomes, with significant health and societal implications for aging populations. These outcomes are not included in current epidemiological models. We aimed to develop an epidemiological model to project incidence and prevalence of stroke, poststroke CIND and dementia, and life expectancy, in Ireland to 2035, informing policy and service planning. Methods: We developed a probabilistic Markov model (the StrokeCog model) applied to the Irish population aged 40 to 89 years to 2035. Data sources included official population and hospital-episode statistics, longitudinal cohort studies, and published estimates. Key assumptions were varied in sensitivity analysis. Results were externally validated against independent sources. The model tracks poststroke progression into health states characterized by no cognitive impairment, CIND, dementia, disability, stroke recurrence, and death. Results: We projected 69 051 people with prevalent stroke in Ireland in 2035 (22.0 per 1000 population [95% CI, 20.8–23.1]), with 25 274 (8.0 per 1000 population [95% CI, 7.1–9.0]) of those projected to have poststroke CIND, and 12 442 having poststroke dementia (4.0 per 1000 population [95% CI, 3.2–4.8]). We projected 8725 annual incident strokes in 2035 (2.8 per 1000 population [95% CI, 2.7–2.9]), with 3832 of these having CIND (1.2 per 1000 population [95% CI, 1.1–1.3]), and 1715 with dementia (0.5 per 1000 population [95% CI, 0.5–0.6]). Life expectancy for stroke survivors at age 50 was 23.4 years (95% CI, 22.3–24.5) for women and 20.7 (95% CI, 19.5–21.9) for men. Conclusions: This novel epidemiological model of stroke, poststroke CIND, and dementia draws on the best available evidence. Sensitivity analysis indicated that findings were robust to assumptions, and where there was uncertainty a conservative approach was taken. The StrokeCog model is a useful tool for service planning and cost-effectiveness analysis and is available for adaptation to other national contexts. Abstract : Supplemental Digital Content is available in the text.